A escrita e reescrita de artigos de opinião em sala de aula : idas e vindas de um processo - Tassan, Sabrina Pinto Ferraz (2015)
Knowing how to verbally act in a protagonist way, in other words, knowing how to contend, position yourself critically, recognizing that the speeches are socially and historically placed, it has become essential in order to meet the demands of a society immerse in the institutionalized literacy methods. Thus, this research theme is the practice of reading and production of opinion articles in the classroom and aims to examine methodologies that purport to assist these language practices in primary school. Thus, we investigated the production of the opinion piece as a support mechanism for reflection on controversial issues under discussion in society, supported by didactic sequence, as well as the guiding ticket, dialogical procedure of support in the rewriting process. For this, we seek first the theoretical foundations that underlie the design of text - genres, according to Bakthin (2003), Marcuschi (2008); didactic sequence, by Dolz e Schneuwly (2010); advisor ticket (textual - interactive tickets) according to Ruiz (2010); argumentation, according to Charaudeau (2010); and Textual and rolling according Bronckart (2012). From this perspective, we intend to analyze, from the context of production of opinion articles produced by high school students, the first version in comparison with the second version performed during the production process. This analytical work allows us to see how reading and discussion of the topic are paramount to that writing can be effected as a practice that helps in critical emancipation of the student, especially because it is a genre that is organized based on themes controversial and therefore requires analytical and reflective positioning.